Evolutionary recycling of sex chromosomes in Neotropical Melanoplinae - Castillo, Elio Rodrigo Daniel (2014)
Orthopterans are a fascinating group of insects in multiple ways. My own research focuses on the evolutionary relationships of South American acridoid grasshoppers with emphasis in the Melanoplinae. In this respect, evidences from different research areas, such as taxonomy, morphometrics, molecular genetics, and cytogenetics are of relevance for the understanding of the evolutionary history of these species, which is my main objective. In this report I will summarize some cytogenetic characteristics of melanoplines and highlight their biological relevance.